Blockchain for 5G healthcare applications security and privacy solutions - Tanwar, Sudeep (Institution of Engineering and Technology, 2022)
A secured system for Healthcare 4.0 is vital to all stakeholders, including patients and caregivers. Using the new Blockchain system of trusted ledgers would help guarantee authenticity in the multi-access system that is Healthcare 4.0. This is the first comprehensive book that explores how to achieve secure systems for Healthcare 4.0 using Blockchain, with emphasis on the key challenges of privacy and security. The book is organized into four sections. The first section is focused on 5G healthcare privacy and security concerns. The second section discusses healthcare architecture and emerging technologies. The third section covers the role of artificial intelligence for data security and privacy in 5G healthcare services. Finally, the last section systematically illustrates the adoption of blockchain in various applications of 5G healthcare. The book is essential reading for all involved in setting up, running, and maintaining healthcare information systems. Engineers, scientists, technologists, developers, designers, and researchers in healthcare technologies, health informatics, security, and information technology will find the content particularly useful.